AI and Data Systems for Credible University CSR: Technology-Driven Impact Measurement and Reporting in Philippine Private Higher Education Institutions - Hazel S. Osano; Anik Yuesti; Joel Arante Alve; Dennis Villasor Madrigal (Lembaga Penelitian dan `Pengabdian Kepada Masyarakat (LPPM), 2026)
In recent years, expectations of accountability in the Philippines have expanded beyond traditional measures of higher education performance such as enrollment, board examination results, and graduate employability. Private higher education institutions were assessed by how responsibly they cared for students, engaged communities, treated employees, and managed institutional resources. Although CSR initiatives were visible across the sector, this study examined how digital systems supported corporate social responsibility in private higher education institutions. A document-based multiple-case approach was used to analyze governance practices, measurement routines, and reporting patterns across institutions. Findings showed that technology strengthened CSR only when measurement and reporting were embedded in governance and decision-making, rather than treated as communication activities. Institutions using clear indicators, assigned responsibility for data, and conducted regular reviews demonstrated stronger alignment between stated commitments and actual practices. Student-centered responsibilities, scholarships, learning support, and welfare services, emerged as the most credible areas of technology-enabled CSR because they were directly experienced by stakeholders. The study found that opaque use of data weakened trust when issues of privacy and fairness were not addressed. Digital systems supported responsible practice only when grounded in accountability, transparency, and institutional care.